ANALISIS DETERMINAN EKSPOR LIGNIT INDONESIA TAHUN 2012-2021 - Raditia, I Wayan Dirsa; Widanta, Anak Agung Bagus Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.04.TAHUN.2024, 2024)
This study aims to analyze; influence of benchmark interest rate and inflation on the USD exchange rate; influence of benchmark interest rate, inflation, coal price reference, and the USD exchange rate on the volume of Indonesia's lignite exports; whether the USD exchange rate mediates influence of benchmark interest rate and inflation on volume of Indonesia's lignite exports. This study uses monthly time series data from 2012-2021 so that 120 observations are obtained, technique used is path analysis. Research shows; 1) the benchmark interest rate and inflation have a negative significant effect on the USD exchange rate in 2012-2021; 2) the benchmark interest rate has a negative significant effect on the volume of Indonesia's lignite exports in 2012-2021, while inflation has no significant effect; 3) the USD exchange rate mediates the influence of the benchmark interest rate and inflation on the volume of Indonesia's lignite exports in 2012-2021.